Handbook of research on synthesizing human emotion in intelligent systems and robotics - Vallverdu, Jordi (Hershey, PA : Information Science Reference, an imprint of IGI Global, 2015)
'This book presents a solid framework for taking human-robot interaction closer to its full potential, presenting a close look at all the factors involved in modeling emotions and applying a thorough understanding of human emotional recognition to technology'--
Includes bibliographical references and index.
Keywords: Human-computer interaction; Human engineering; Robotics